Analysis Of the Impact Test of Brass Material Using the Charpy Method - Akhmad Khakiki; Wisma Soedarmadji (International Journal of Health Engineering and Technology, 2025)
The rapid development of industries such as construction, manufacturing, and automotive requires materials with excellent mechanical properties, particularly impact resistance. Brass, a copper-zinc alloy (Cu–Zn), is widely applied due to its ductility, corrosion resistance, thermal conductivity, and manufacturability. However, quantitative data on the dynamic toughness of brass remain limited and vary significantly depending on composition, heat treatment, and testing conditions. This study aims to analyze the impact toughness of brass using the Charpy impact test method, evaluate the accuracy and consistency of the results, and identify factors influencing impact resistance. The research employed a quantitative experimental method with a controlled design. The population consisted of α-brass specimens, while the samples were several homogeneous and representative test pieces without additional heat treatment or cold working. The main instrument used was a Charpy impact testing machine with notched specimens, and data were analyzed using descriptive statistics, calculating average absorbed energy and energy per unit area. The results revealed that brass exhibits stable performance under impact loading, with an average absorbed energy of 113–115 J and energy per unit area of 0.961–0.979 J/mm². The findings confirm that α-brass with less than 35% zinc content possesses a homogeneous microstructure, contributing to high ductility and toughness. In conclusion, brass is a reliable and economical material for light to medium engineering applications, although further studies are recommended to explore the effects of heat treatment, cold working, and alloy variations on its impact toughness.